PSYCHOLOGICAL AND PEDAGOGICAL CONDITIONS FOR CREATING A CREATIVE ENVIRONMENT IN ART EDUCATION. - Xasanova Sitora Shuhrat qizi, (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
ANNOTATION This article explores the psychological and pedagogical conditions for creating a creative environment in the system of art education. It highlights the importance of developing students’ creative potential, artistic thinking, and emotional perception through favorable learning environments. The study emphasizes that the formation of a creative atmosphere in art classes depends on the teacher’s professional competence, pedagogical culture, motivation, and the use of interactive and innovative teaching methods. Drawing on the works of S.A. Shovdirov and other modern researchers, the article discusses how a psychologically safe, emotionally supportive, and aesthetically rich environment contributes to the effective development of students’ creative abilities and artistic literacy.